2019
DOI: 10.3389/fmicb.2018.03274
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Pleurotus tuoliensis During Mycelium Physiological Maturation and Exploration on a Potential Indicator of Mycelial Maturation

Abstract: Pleurotus tuoliensis is a valuable and rare edible fungus with extremely high nutritional and medicinal value. However, the relative immaturity of P. tuoliensis cultivation technology leads to fluctuating yields and quality. The main difficulty in P. tuoliensis cultivation is estimate of mycelial maturity. There is currently no measurable indicator that clearly characterizes the physiological maturation of mycelia. The aim of this study was to identify potential indicators of physiological maturation for P. tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Nitrogen can be transported into the fungus’s living cell in the form of amino acids (Mikeš et al 1994 ). The product applied was rich in amino acids, essential during the mycelial maturation stage (Du et al 2019 ). When added to the growing substrate, amino acids, as source of nutrients, could be more easily assimilated than proteins present in the initial substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen can be transported into the fungus’s living cell in the form of amino acids (Mikeš et al 1994 ). The product applied was rich in amino acids, essential during the mycelial maturation stage (Du et al 2019 ). When added to the growing substrate, amino acids, as source of nutrients, could be more easily assimilated than proteins present in the initial substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolome analysis of physiological maturation of P. tuoliensis mycelia also revealed similar metabolism phenomenon. Metabolites enriched on pyrimidine synthesis were significantly abundant in mature P. tuoliensis mycelia, such as CMP and cytosine, which are indicative of the high demand for rapid nucleotide synthesis during physiological maturation [7].…”
Section: Discussionmentioning
confidence: 99%
“…After 20 days of induction, CA-asp content in mycelia were determined every two days. After CA-asp content in mycelia reached 0.9 g/L, mycelia reached physiological maturation [7]. We then randomly selected three cultivation bottles and transferred the mycelia to three corresponding tubes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 , 15 It was reported that nontargeted metabonomic methods have been used to distinguish the metabolite composition of different parts of Ganoderma lucidum and different growth and development stages of Pleurotus tuoliensis . 16 The available software, algorithms, and experimental methods have now made metabonomics a good tool for comparing the chemical metabolites of fruiting bodies on different tree species.…”
Section: Introductionmentioning
confidence: 99%